O quadro de escrever como recurso facilitador de interação e aprendizagem dos alunos no processo de avaliação - MICCIONE, Domênico Góes (2006)
This study the following goals: 1. To investigate the students learning results from an evaluation experience, using the blackboard as a way of making it easier. 2. To use procedures that make the student participation in evaluation activities on the blackboard possible. It was developed in a high school-first-year group from a federal public school of Pará. The results indicate that the blackboard use in an interaction way makes the students learning easier when pedagogy didactic aspects that do not depend on the tendencies in Mathematics Education, such as the diagnosis evaluation, social interaction, didactic contract, error / mistake and the epistemology obstacles are considered. Finally, we conclude that the blackboard must have its meaning established again for the mathematics teacher pedagogy practice.